Systemic Lupus Erythematosus Disease: An Overview of the Clinical Approach to Pathogenesis, Diagnosis, and Treatment - Saurabh Nimesh; Md. Iftekhar Ahmad; Shikhka Dhama; Pradeep Kumar; Muhammad Akram; Neda Esmaeili Nejad Hasaroeih (Borneo Journal of Pharmacy, 2021)
The systemic lupus erythematosus (SLE), commonly known as Lupus, is a rare and complex multisystem autoimmune disease where one’s immune system is overactive, and the body attacks its organ systems. SLE is a historically old disease described already in antiquity; it is an example of a chronic disease with physical, psychological, financial, and social implications for individuals diagnosed. It has inspired medical and basic biological scientists that focus on molecular biology, basic immunology, immunopathology, clinical science, genetics, and epidemiology. The syndrome is real in its existence-although hidden behind obstacles, cumbersome for patients and clinicians, and rebellious for scientists. There is currently no cure for SLE. The goal of treatment is to ease symptoms. This article will review information on the general approach to SLE therapy, focusing on currently approved therapies and novel approaches that might be used in the future.